Pengaruh Kombinasi Pupuk Anorganik NPK dan POC Urin Kelinci Terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassicarapa L.) Varietas Nauli F1 - Zahiri, Miftah (JURNAL AGROPLASMA, 2023)
Pakcoy (Brassica rapa L.) or also called spoon mustard is a type of vegetable horticultural plant that belongs to the Brassicaceae family. Pakcoy is a leaf vegetable plant that belongs to the same genus as mustard. The use of rabbit urine as liquid organic fertilizer is not only beneficial for increasing soil fertility, it can also reduce costs that must be incurred in farming activities. The aims of studi is to obtain a combination dosage of NPK inorganic fertilizer and rabbit urine organic fertilizer that can provide the best growth and yield for pakcoy plants. This research was carried out in Payungsari Village, Pedes District, Karawang Regency, West Java Province, in May – June 2022 The experimental method distric experimental method using a single factor Randomized Block Design (RBD), with 3 replications, A 0 (control), B (150 kg/ha + 10 l/ha), C (150 kg/ha + 20 l/ha), D (150 kg/ha + 30 l/ha), E (200 kg/ha + 10 l/ha), F (200 kg/ha + 20 l/ha+, G (200 kg/ha + 30 l/ha), H (250 kg/ha + 10 l/ha), I (250 kg/ha + 20 l/ha) and J (250 kg/ha + 30 l/ha). Data were analyzed statistically with the F table 5% test and Duncan's New Multiple Range Test (DMRT) at the 5% level. The hight yield with root and without root of 150,08 g/plant and 142,38 g/plant, respectired was obtained by treatment J (250 kg/ha NPK + 30 l/ha POC rabbit urine). This achievement was significant atechment with of treatment A (control) and was not significant district with other achievement.Keywords: POC rabbit urine, rabbit urine, pakcoy, growth and yield